Peran Quality of Work Life dalam Membangun Organizational Citizenship Behaviour melalui Sense of Belonging - Asep Budiman; Gusti Tia Ardiani; Indi Ramadhani (Jurnal Bisnis dan Ekonomi, 2020)
This research is based on the phenomenon of Human Resources problems in rural bank including lack of management. Some other problems that are faced by the organization is working at rural bank has not been an option for the employees. The incompatibility of compensation with expectations and the limited size of the rural bank market induce many potential employees to work at commercial banks. This caused the increase of employee turnover. Moreover, it is normal that potential employees are often attracted by greater and more appropriate compensation that motivated them to quit and find better work place. The model developed in this research was to test the role of quality of work life in building organizational citizenship behaviour through sense of belonging at rural bank in Tasikmalaya District. The result of this research is aimed at helping rural bank in Tasikmalaya District in knowing the role of quality of work life in building organizational citizenship behaviour through sense of belonging. The research method used was a survey method, with data collection techniques using a questionnaire given to 180 employees of rural bank in Tasikmalaya District. The data analysis and hypothesis testing in this study used mediation variable regression analysis (product of coefficient method). The results of this study declared that there was a positive effect on quality of work life on sense of belonging. Furthermore, the sense of belonging mediating a causal relationship between quality of work life on organizational citizenship behaviour.